Antivenin‐associated serum sickness in a dog. Issue 5 (26th August 2019) - Lee, Benjamin M.; Zersen, Kristin M.; Schissler, Jennifer R.; Sullivan, Lauren A.
Abstract: Objective: To describe a case of documented serum sickness in a dog following administration of a single dose of a novel antivenin crotalidae polyvalent. Case Summary: A 4‐year‐old female neutered mixed breed dog developed recurrent signs of hypersensitivity (swelling, edema, urticaria/hives, gastrointestinal signs, vasculitis) at 1 and 2 weeks following administration of a single unit of a novel antivenin crotalidae polyvalent plasma product. Both episodes were treated with antihistamines and glucocorticoids and signs improved rapidly, with a prolonged course of glucocorticoids and antihistamines administered following the second occurrence. Diagnosis of serum sickness was based on clinical appearance of delayed hypersensitivity following exposure to novel biologic product, absence of other inciting cause of hypersensitivity, complement testing, and skin biopsies confirming vasculitis. New or Unique Information Provided: This case documents the first report of delayed hypersensitivity with a novel antivenin plasma product. This is the only case report of serum sickness to a single unit of antivenin. Additionally, the dog developed recurrence of hypersensitivity following the initial episode at 1 week; appropriate identification and prolonged treatment could have prevented recurrence and additional hospitalization. Cost and benefit analysis should be considered with antivenin administration.